High mannose-binding antiviral lectin PFL from Pseudomonas fluorescens Pf0-1 promotes cell death of gastric cancer cell MKN28 via interaction with α2-integrin. - Yuichiro Sato (Public Library of Science (PLoS), 2012)
Novel anti-HIV lectin family which shows a strict binding specificity for high mannose glycans has been found in lower organisms. The bacterial orthologue has been identified in the genome of Pseudomonas fluorescens Pf0-1 and the gene coding a putative lectin was cloned, expressed in Escherichia coli and purified by one step gel filtration. Glycan array screening of the recombinant lectin, termed PFL, has revealed that PFL preferentially recognizes high mannose glycans with α1-3 Man that was highly exposed at the D2 position. In contrast, masking of this α1-3 Man with α1-2 Man dramatically impaired lectin-carbohydrate interactions. Reducing terminal disaccharide, GlcNAc-GlcNAc of high mannose glycans was also essential for PFL-binding. PFL showed a potent anti-influenza virus activity by inhibiting the virus entry into cells at doses of low nanomolar concentration. At micromolar concentration or higher, PFL showed a cytotoxicity accompanying loss of the cell adhesion against human gastric cancer MKN28 cells. The cell surface molecule to which PFL bound was co-precipitated with biotin-labeled PFL and identified as integrin α2 by peptide mass fingerprinting using MALDI-TOF mass spectrometry. Intriguingly, upon treatment with exogenous PFL, integrin α2 on the cell surface underwent rapid internalization to the cytoplasm and accumulated to perinuclear region, together with the bound PFL. The resulting loss of cell adherence would trigger a signaling pathway that induced anoikis-like cell death. These events were effectively inhibited by pretreatment of PFL with mannnan, indicating the involvement of high mannose glycans on PFL-induced cell death that was triggered by PFL-integrin α2 interactions.